DEVELOPMENT OF LEARNING ACTIVITY PACKAGE USING THE JIGSAW TECHNIQUE COMBINED WITH CONCEPT MAPPING TO ENHANCE GROUP WORK SKILLS ON THE GEOGRAPHY OF NORTH AMERICA UNDER GEOGRAPHY SUBSTANCES, SOCIAL STUDIES, RELIGION AND CULTURE OF MATTHAYOMSUKSA 3 THUNG MAPHRAO WITTHAYA SCHOOL, THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE PHANGNGA, PHUKET, AND RANONG - Boonson, Wilairat; Thongkanluang, Sirisawas; Songsawat, Kritsanee (Journal of MCU Nakhondhat, 2024)
This research article aimed to 1) develop a learning activity package with efficiency values and efficacy index meeting the criteria of 80/80 and 0.50 or higher, 2) compare the academic achievement before and after the use of the learning activity package, and 3) enhance the group work skills of students using the learning activity package. The scope of the research included the geography of North America as part of the geography curriculum of the Core Basic Education Curriculum 2008 (Revised 2017), with learning standards and indicators S 5.1 M.3/1, S 5.2 M.3/1, and S 5.2 M.3/2, utilizing a single - group pretest - posttest experimental design. The population included of 60 Matthayomsuksa 3 students from Thung Maphrao Witthaya School and the sample group of 30 students from Matthayomsuksa 3/1 selected by cluster random sampling. The research instruments included 6 sets of learning management plans and the learning activity package with an average accuracy and appropriateness score between 4.78 - 4.88; a 40 - item achievement test with a difficulty index ranging between 0.33 - 0.73, discrimination index between 0.20 - 0.47, and reliability at 0.84; and a group work ability assessment form with IOC at 1.00. The statistics for data analysis included percentage, mean, standard deviation, and t - test. The research found that 1) the learning activity package exceeded the set efficiency criteria with scores of 83.61/82.75 and an efficacy index of 0.77, 2) the post-learning achievement scores with the learning activity package had a mean of 33.63, significantly higher than the pre-learning mean of 11.23 (p < .01), and 3) the group work skills of students using the learning activity package had a mean of 2.94, indicating a good level.